2014
DOI: 10.1007/s11064-014-1483-z
|View full text |Cite
|
Sign up to set email alerts
|

Osthole, a Natural Coumarin Improves Cognitive Impairments and BBB Dysfunction After Transient Global Brain Ischemia in C57 BL/6J Mice: Involvement of Nrf2 Pathway

Abstract: Oxidative stress and blood-brain barrier (BBB) disruption play important roles in cerebral ischemic pathogenesis and may represent targets for treatment. Earlier studies have shown that osthole, a main active constituent isolated from Cnidium monnieri (L.) Cusson, could be considered as an attractive therapeutic agent in the treatment of ischemic stroke. However, the mechanism underlying the protective effect remains vague. In this study we aimed to investigate the effect of osthole on transient cerebral ische… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…In another study, osthole protected against LPS-induced inflammation in BV2 cells via NF-κB suppression and upregulation of the Nrf2/HO-1 pathway dose dependently [245]. Additionally, osthole exerted neuroprotective effects against global cerebral I/R injury by reducing oxidative stress via the upregulation of the Nrf2/HO-1 signaling pathway [246]. The renoprotective effect of osthole against accelerated focal segmental glomerulosclerosis was mediated via Nrf2 activation and subsequently downregulation of the NF-κB-mediated COX-2 expression [247].…”
Section: Fraxin Fraxin (7-hydroxy-6-methoxy-8-[(2s3r4s5s 6rmentioning
confidence: 95%
“…In another study, osthole protected against LPS-induced inflammation in BV2 cells via NF-κB suppression and upregulation of the Nrf2/HO-1 pathway dose dependently [245]. Additionally, osthole exerted neuroprotective effects against global cerebral I/R injury by reducing oxidative stress via the upregulation of the Nrf2/HO-1 signaling pathway [246]. The renoprotective effect of osthole against accelerated focal segmental glomerulosclerosis was mediated via Nrf2 activation and subsequently downregulation of the NF-κB-mediated COX-2 expression [247].…”
Section: Fraxin Fraxin (7-hydroxy-6-methoxy-8-[(2s3r4s5s 6rmentioning
confidence: 95%
“…The effective component, 7‐methoxy‐8‐(3‐methyl‐2‐butenyl)‐2H‐1‐benzopyran‐2‐one, is a natural coumarin first derived from the plant Cnidium monnieri (L.) Cusson (Figure A) . Recently, its potential antioxidant, immunomodulation, anti‐inflammatory, and anticancer effects have been explored . Osthole exerts neuroprotective effects against neurodegeneration, alleviating brain injury and decline in neurobehavioral function caused by both chronic and acute ischemia .…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of emodin has been extensively researched, and osthole, as an emerging Chinese medicine, has been widely investigated in recent years. Hao et al (25) demonstrated that osthole exhibited a therapeutic effect on pulmonary fibrosis, while Chen et al (26) reported beneficial effects of osthole on cognitive impairment in animals, which may occur via the Nrf2 pathway. These results indicate that osthole may act on the nervous system.…”
Section: Discussionmentioning
confidence: 99%